Memahami Gaya Belajar untuk meningkatkan Potensi Anak - Mufidah, Luk-Luk Nur (Martabat: Jurnal Perempuan dan Anak, 2017)
Every human being born into this world is always different from each other. Both physical form, behavior, traits, and various other habits. No human being has the same physical form, behavior and nature even though the twins. One thing we need to know together is that every human being has a way of absorbing and processing the information it receives in different ways from each other. It really depends on the learning style. Learning styles are the way each person takes in absorbing new and difficult information, how they concentrate, process and store information that enters the brain. Understanding the child's learning styles will support his success. The best way to stimulate learning is to give full support to their interests and provide a variety of educative games to support learning.